Identification of Land Resource Potential for Agricultural Landscape Planning Using Land Capability Evaluation Approach and GIS Application (a Case in Central Kalimantan Province, Indonesia) - Andy Bhermana; Suparman Suparman; Hijrah Tunisa; Bambang Hendro Sunarminto (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
Land allocation for agricultural lands is required when the region have potency to be developed while the same time, conservation aspects are still considered. Central Kalimantan Province with total areas of 15, 451, 287 hectares has potential land available for agricultural development. At initial stage, with a landscape scale, land resource potential is needed to be assessed for planning purposes. The aimed of this study was to design the spatial concept of agricultural landscape planning on sustained basis. Methodology used in this include concept of land capability evalution (LCE) approach and geographic information system (GIS) application. The result of evaluation showed that Central Kalimantan was classified into 6 land capability classes i.e class II, III, IV, VI, VII, and VIII with several limiting factors such as peat depth, drainage, slope, and texture. Within GIS environment, the result of spatial analysis shown that total areas of agricultural land region was 9,571,231 hectares or 61.95% of total Central Kalimantan province. This indicates that the lands are still widely available for agricultural development. These areas are located not only in wetlands typology but also found in dryland areas. Specific program that specific to location can then be formulated in order to develop the areas.